2021
DOI: 10.3390/medicina57060540
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cerebral Palsy in Moldova

Abstract: Background and Objectives: This is the first study assessing risk factors for cerebral palsy (CP) among children born in Moldova. The aim of this study was to identify and describe risk factors for cerebral palsy (CP) among children born in Moldova, which is one of the low-middle income countries in Europe. Materials and Methods: We identified 351 children with CP born during 2009 and 2010 in Moldova. Detailed information on 417 children without CP served as a reference group. Logistic regression analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The cause of preterm births can also be examined as a subject of a separate study. Gincota et al [ 16 ] reported in their study that low socio-economic status was associated with CP. In our study, according to the mothers’ declarations, the income levels of these families were low at a rate of 73.3% and at a moderate level with a rate of 24.8%, and low socioeconomic status was remarkable in terms of CP risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of preterm births can also be examined as a subject of a separate study. Gincota et al [ 16 ] reported in their study that low socio-economic status was associated with CP. In our study, according to the mothers’ declarations, the income levels of these families were low at a rate of 73.3% and at a moderate level with a rate of 24.8%, and low socioeconomic status was remarkable in terms of CP risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Parental risk factors, primarily reported on the maternal side, include hypertension, 12 diabetes mellitus, 10,12 infection or chorioamnionitis, 12 alcohol consumption during pregnancy, 13 parent aged older than 35 years, 13 preeclampsia, 10 prolonged rupture of membranes, 10 and birth by Cesarean section. 8 Infant risk factors are low birthweight, 11,12 neonatal infections, 10 being born preterm, 11 malformations, 8,10 being born small for gestational age, 8,13 admission to a neonatal intensive care unit, 8 meconium aspiration, 10 birth asphyxia, 12 respiratory distress syndrome, 9 multiple gestation, 12,13 intraventricular hemorrhage (IVH), 10 neonatal encephalopathy, 10,12 hyperbilirubinemia, 10,13 and male sex. 13 Additionally, the research methods used varied, with most studies using relatively small sample sizes.…”
Section: Risk Factors For Cerebral Palsy In Children In Taiwanmentioning
confidence: 99%
“…Systematic reviews, meta-analyses, and individual studies investigated the potential risk factors of CP, [8][9][10][11][12][13] but a consensus has yet to be reached. Generally, risk factors can be…”
mentioning
confidence: 99%
“…In a study conducted in Moldova, a low-income country, among 351 individuals with CP, several significant risk factors were identified. These included maternal alcohol consumption during pregnancy [odds ratio (OR) 1.7, P=0.002], maternal hypertension (OR 2.0, P<0.001), living in rural areas (OR 1.6, P<0.001), maternal age of more than 35 years old (OR 0.6, P=0.001), maternal epilepsy (OR 4.3, P<0.001), breech delivery (OR 3.1, P=0.001), home births (OR 6.3, P=0.001), umbilical cord around neck (OR 2.2, P<0.001), assisted vaginal delivery (OR 3.1, P<0.001), male gender (OR 1.3, P<0.001), small gestational age (SGA) (OR 1.3, P=0.027), multiple gestations (OR 1.7, P<0.001) and hyperbilirubinemia (OR 4.5, P<0.001) ( 3 ). CP classification, proposed by Ingram and Hagberg, encompasses types of neurological syndromes, affected sites, and severity of symptoms.…”
Section: Introductionmentioning
confidence: 99%